Поляки на службе русского царя - Лазарян, Сергей (Acta Polono-Ruthenica, 2021)
This article deals with Poles who served in the Caucasus in the Russian troops or as civilian officials throughout almost the entire 19th century. Regardless of how the Poles came there, of their own free will, as representatives of ‟economic emigration”, or, conversely, as recruits-conscripts or prisoners, they contributed a lot to the economic and socio-cultural development of the land, which has been identified with the roots of the European civilization. While studying the biographies of such Poles, it can be noted with great confidence that they became a vital part of the life of the Caucasian region, having inscribed their names in the annals of local history. It is extremely difficult to identify the actual number of Poles who participated in the conquest of the Caucasus, just as it is difficult to say whether these people were aware of their role in this process, but the result is indisputable – the Poles helped Russia to conquer this region, turning it into an integral part of the Russian state.